Sekam yang Ditiup Angin - Sapto Sunariyanti (SEKOLAH TINGGI TEOLOGI KIBAID MAKALE, 2026)
This study highlights Psalm 1:4–5, a verse that is often overlooked in academic studies, but has significant symbolic, social, and theological significance. The background of this research arises from the lack of studies that examine in depth the symbols of the chaff (ḥaḇal) and the wind (ruaḥ), social separation (qahal), and God's judgment (mishpat) in an integrated manner. The research problem is formulated as: how do verses 4–5 of Psalm 1 shape the understanding of the mortality of the wicked, their social isolation, and the consequences of divine judgment? The research uses an expository-theological qualitative method that combines analysis of Hebrew texts, symbolic studies, and social and theological interpretations. The results show that wicked people are portrayed as chaff blown by the wind, emphasizing moral instability, social alienation, and spiritual mortality. Their social separation serves as a mechanism for the preservation of the community, while God's judgment affirms moral and eschatological consequences. This research presents methodological novelty through a holistic approach that integrates symbolic, social, and theological dimensions simultaneously, in contrast to previous studies that tend to be partial. In conclusion, Psalm 1:4–5 is not just an individual moral text, but a holistic guide to spiritual and social life, relevant to contemporary readers who want to understand the relationship between personal integrity, community contribution, and moral responsibility.